Impacts of CO(2) elevation on the physiology and seed quality of soybean - Zheng, Guowei (Plant Divers, 2019)
Understanding the responses of crops to elevated atmospheric carbon dioxide concentrations (E[CO(2)]) is very important in terms of global food supplies. The present study investigates the effects of CO(2) enrichment (to 800 μmol mol(−1)) on the physiology of soybean plants and the nutritional value of their seeds under growth chamber conditions. The photosynthesis of soybean was significantly promoted by E[CO(2)] at all growth stages, but leaf area and specific leaf weight were not affected. The levels of mineral elements in the leaves decreased under E[CO(2)]. The soil properties after soybean cultivation under E[CO(2)] were not affected, except for a decrease in available potassium. Moreover, the levels of soluble sugars in the seeds were not affected by E[CO(2)], but the levels of natural antioxidants decreased. In addition, the level of oleic acid decreased under E[CO(2)]. However, levels of fatty acid peroxidation and saturation were maintained. In conclusion, E[CO(2)] appears to have positive effects on the growth of cultivated soybean plants, but its influence on the nutritional values of soybean seeds is complex.